The Kingdom of God in Romans - Grindheim, Sigurd 1968- (2017)
It is commonly assumed that there is no direct connection between Jesus’ teaching on the kingdom of God and the theology of Paul. By inquiring after both conceptual and terminological links, however, this article argues that Jesus’ teaching on the kingdom has left clear traces in Paul’s writings. Jesus’ proclamation of the present rule of God, manifested in his own victory over evil spirits, is given an ethical interpretation by Paul, who sees the kingly rule of God expressed in believers’ victory over sin.
Keywords: Bible. New Testament -- Ethics; Bible. New Testament -- Theology; Bible. Romans -- Theology; Jesus Christ; Kingdom of God -- Biblical teaching; Paul, Saint, Apostle